English and its language policy in different countries - Asadova, Nurana Rovshan (Technium Social Sciences Journal, 2023)
In the modern world, English has become widespread only in the “inner circle” countries (Great Britain, Ireland, USA, Canada, Australia and New Zealand) where English is the native language of the population. English is also actively used in outer circle countries. Countries in this circle include India, Nigeria, Bangladesh, Pakistan, Malaysia, Kenya, South Africa, etc. In the “Outer Circle” countries, English is not the native language of a significant part of the population, but it plays an important role in government actions and daily communication. There are also “expanding circle” countries (Russia, China, Japan, Korea, Egypt, Germany, France, etc.) where English is not the native language of the majority of the population and is not used in public administration. In these countries, English is used in some fields of activity such as education, business, science, culture and tourism.